A new method for ageing wild boar using dental measures. (March 2016) - Gonçalves, Pilar; Risco, David; Fernández-Llario, Pedro; Barquero-Pérez, Oscar; Serrano, Emmanuel; Hermoso-de-Mendoza, Javier; Mateos, Concha
Abstract: Over the last decades, wild boar ( Sus scrofa ) populations in Europe have increased with impacts on agriculture, livestock and biodiversity. Thus, changes in population management for wild boar are increasingly important. Knowledge of the age structure of the population is crucial to designing effective management plans. However, the costs and efforts required to estimate the age of wild boar, primarily in the oldest animals, is problematic for managers and researchers. Here, we describe a new method to estimate wild boar age based on simple dental measures (the external aperture of the pulp cavity, root length and crown length from primary and secondary incisors). Our study was based on data from 93 wild boar of known age belonging to two different populations in central and south-eastern Spain. We propose a model based on Boosted Regression Trees (BRT). Our results show a final age estimation model that included all the explanatory variables proposed (dental measures) and showed a high percentage of estimated deviance (61%), obtained by cross-validation. Thus, at least in Iberian wild boar populations, our method constitutes a low-cost and reliable method for wild boar age estimation.